2015
DOI: 10.1089/end.2014.0570
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Lithotripsy Does Not Impair Renal Function in a Swine Model of Metabolic Syndrome

Abstract: Purpose: To determine whether shock wave lithotripsy (SWL) may be a risk factor for renal functional impairment in a swine model of metabolic syndrome (MetS). Materials and Methods: Nine-month-old female Ossabaw pigs were fed an excess calorie atherogenic diet to induce MetS. At 15 months of age, the MetS pigs were treated with 2000 SWs or an overtreatment dose of 4000 SWs targeted at the upper pole calyx of the left kidney (24 kV at 120 SWs/min using the unmodified Dornier HM3 lithotripter; n = 5-6 per treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The two pigs in the present series of experiments are a subset of the animals assessed for glucose tolerance and insulin resistance before and after SWL in a recently published study [12]. Details of renal function and renal pathology of such SWL-treated MetS pigs has also been published [13]. …”
Section: Methodsmentioning
confidence: 99%
“…The two pigs in the present series of experiments are a subset of the animals assessed for glucose tolerance and insulin resistance before and after SWL in a recently published study [12]. Details of renal function and renal pathology of such SWL-treated MetS pigs has also been published [13]. …”
Section: Methodsmentioning
confidence: 99%
“…SWL is a less invasive treatment modality compared to RIRS, however, RIRS seems to have higher success and lower re-treatment rates (18). All these interventions affect the renal function and there are fewer studies evaluating and comparing these aspects (10,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, a few reports evaluating long-term outcomes of SWL treatment in patients with chronic renal failure also suggest that SWL is a safe treatment modality (21,22). In their animal model of metabolic syndrome, Handa et al (20) reported that a single session of SWL did not result in renal impairment, even in the presence of metabolic syndrome. As a result of the first study in the literature investigating the effect of RIRS on renal functions, univariate cox regression analysis revealed that multiple procedures and pre-existing chronic kidney disease were significant factors for renal deterioration (19).…”
Section: Discussionmentioning
confidence: 99%
“…The primary acute lesion is trauma to blood vessels with extra-vasculature pooling of blood within the renal tissue. Tissue damage from SWL also extends to the tubules and glomeruli [2,3], and the production and release of inflammatory and oxidative stress mediators [4,5], which can result in fibrosis and loss of functional tissue [2,6,7]. Such injury from SWL has been linked to adverse patient outcomes, e.g.…”
Section: Introductionmentioning
confidence: 99%